2023
DOI: 10.1101/2023.02.05.527176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implicit auditory memory in older listeners: from encoding to 6-month retention

Abstract: Any listening task, from sound recognition to sound-based communication, rests on auditory sensory memory which is known to decline in healthy ageing. However, whether this decline maps on to multiple components and stages of auditory memory remains poorly characterised. We tested ageing effects on implicit auditory memory for rapid tone-patterns in an online unsupervised longitudinal study (day 1, day 8 and 6-month sessions) including younger (aged 20-30) and older adults (aged 60-70). The test required parti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 162 publications
1
4
0
Order By: Relevance
“…Previous work further shows that individuals show behavioral correlates of memory for random noise or tone structure in sounds even days and weeks after exposure (Agus et al, 2010;Viswanathan et al, 2016;Bianco et al, 2020;Bianco et al, 2023). That the brain responds with similar magnitude to a reoccurring noise snippet following an interruption compared to a snippet that is part of a regular, noninterrupted sequence is consistent with a memory representation for a noise snippet that lasts long once the representation has been established.…”
Section: Invariant Neural Response To the Reoccurring Frozen Noise Sn...supporting
confidence: 54%
See 2 more Smart Citations
“…Previous work further shows that individuals show behavioral correlates of memory for random noise or tone structure in sounds even days and weeks after exposure (Agus et al, 2010;Viswanathan et al, 2016;Bianco et al, 2020;Bianco et al, 2023). That the brain responds with similar magnitude to a reoccurring noise snippet following an interruption compared to a snippet that is part of a regular, noninterrupted sequence is consistent with a memory representation for a noise snippet that lasts long once the representation has been established.…”
Section: Invariant Neural Response To the Reoccurring Frozen Noise Sn...supporting
confidence: 54%
“…Several previous works have shown that individuals better detect a noise snippet repetition when the snippet that is repeated recurs across trials compared to a snippet that does not recur (Agus et al, 2010; Agus and Pressnitzer, 2013; Andrillon et al, 2015; Andrillon et al, 2017; Dauer et al, 2022). Previous work further shows that individuals show behavioral correlates of memory for random noise or tone structure in sounds even days and weeks after exposure (Agus et al, 2010; Viswanathan et al, 2016; Bianco et al, 2020; Bianco et al, 2023). That the brain responds with similar magnitude to a reoccurring noise snippet following an interruption compared to a snippet that is part of a regular, non-interrupted sequence is consistent with a memory representation for a noise snippet that lasts long once the representation has been established.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To determine that a regular pattern has emerged, the auditory system must maintain the recently encountered information in some form of memory store, compare incoming information to this representation, and detect pattern repetition. This stimulus has been extensively used to study auditory short-term memory and its neural underpinnings ( Barascud et al, 2016 ; Barczak et al, 2018 ; Bianco et al, 2023 , 2020 ; Herrmann et al, 2019 ; Southwell & Chait, 2018 ). An additional task (TP-COMP), using similar stimuli, required active memory maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…We use a tone pattern detection task (TP-DETECT; Figure 1 ) to tap the automatic aSM components. This paradigm is extensively used to understand low-level aSM ( Barascud et al, 2016 ; Bianco et al, 2020, 2023 ; Herrmann et al, 2021 ; Milne et al, 2021 ; Southwell et al, 2017 ). Short tones forming patterns are presented at time scales resembling those in speech (20-Hz tone presentation rate, 2-Hz pattern rate) ( Rosen, 1992 ).…”
Section: Introductionmentioning
confidence: 99%